Postawa religijna a relacje interpersonalne katechizowanej młodzieży gimnazjalnej - Stach-Hejosz, Magdalena (Śląskie Studia Historyczno-Teologiczne, 2011)
The young people attacked by confusing informations coming usually from mass media, are exposed for harmful influence of present moral crisis. Often being manipulated, the youth isolate catholic moral values from “things of this world”. Moral values are closed in private life sphere. That is why, according to the catholic preceptors, it’s important to form religious attitudes as constant and solid reference to the God and to the Church. The Church in care for youth interest has consiousness that crisis of identity experienced by the young people during gymnasial school period could negative effect for their religious atmosphere. This situation can have influence for interpersonal relations. It is confirmed by researches that young people have leak references to the God and to the Church. Immature reference to the God has often connection with immature personality, orientated for support in the same age group. Moreover it may be assumed that recede influence of rustic traditional background for forming religious attitudes among the young. References to the God and the Church, being observed among catechized young people, become their personal choice matter.